2018
DOI: 10.2478/cjf-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Moringa oleifera Leaf Meal as a Replacement for Soybean Meal on Growth, Body Composition and Health Status in Cyprinus carpio Juveniles

Abstract: The growth performance, nutrient utilization and health status of Cyprinus carpio fed various levels of Moringa oleifera leaf meal as a replacement for soybean meal was investigated. Six isonitrogenous diets were formulated with Moringa oleifera leaf meal at 0%, 10%, 20%, 30%, 40% or 50% crude protein replacement. The diets were fed to the fish at 5% body weight to 360 Cyprinus carpio juveniles (8.12±0.21 g) allotted to 18 happas (1 m3) in a completely randomized design for 12 weeks. The results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
(20 reference statements)
4
9
0
Order By: Relevance
“…The best results in this trial came from the partial replacement of shmeal in the sh-fed diet FSM with soybean meal and moringa leaf meal. This supports the ndings of Adeshina et al (2018) and El-Gawad et al (2019), whose studies showed that adding moringa to the diet of Cyprinus carpio and Nile tilapia signi cantly improved the performance of the sh as a whole.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The best results in this trial came from the partial replacement of shmeal in the sh-fed diet FSM with soybean meal and moringa leaf meal. This supports the ndings of Adeshina et al (2018) and El-Gawad et al (2019), whose studies showed that adding moringa to the diet of Cyprinus carpio and Nile tilapia signi cantly improved the performance of the sh as a whole.…”
Section: Discussionsupporting
confidence: 88%
“…The experimental diets improved sh body composition as several studies have similarly reported variations in sh carcass composition between the initial and nal stages that were seen in the current study (Billah et al 2020, Adeshina et al 2018, Vhanalakar & Muley, 2014. When moringa was fed to Cyprinus carpio, they had better body compositions, as reported by Adeshina et al (2018). Fish fed diet FMG showed a noticeably reduced protein carcass composition.…”
Section: Discussionsupporting
confidence: 77%
“…Given that M. oleifera is a locally available year-round in the Philippines, the use of M. oliefera leaves as alternative daily food for farmed abalones has been proposed. Adeshina et al (71) used Moringa leaf meal for Cyprinus carpio and found that supplemented diets can enhance growth at the juvenile period. In addition, Moringa leaf meal significantly improve fish immune response.…”
Section: Effects Of M Oleifera Leaf On Aquatic Animal Performancementioning
confidence: 99%
“…In our study, C. mrigala fed on MOLM based diet at 10% replacement level showed the maximum values of RBCs (2.50×10 3 mm -3 ), WBCs (7.50 ×10 3 mm -3 ), Hb (8.47 g/100 ml) and MCHC (33.94%), afterwards it decreased with the increase in MOLM concentration. Similarly, Adeshina et al (2018) recommended 10% level of MOLM to be incorporated in the diets of common carp at juvenile stage; for maximum growth performance and hematological indices like increased amount of Hb (4.80±0.12g/dL) and RBCs (1.07×10 6 mm -3 ). These indicate the improved oxygen carrying capacity of the blood.…”
Section: Discussionmentioning
confidence: 99%